Development and application of silicon semiconductor γ dose rate monitor - Xu Shaoyi; Li Wei; Liu Xiang (Dianzi Jishu Yingyong)
Silicon semiconductor γ dose rate monitor is widely used in the radioactivity measurement of nuclear facilities. Based on the ongoing localization research and development project, this paper introduces overall design and development of the γ silicon semiconductor dose rate monitor, the main hardware design and software function design of the instrument. At the same time, the main technical parameters of the silicon semiconductor and the gas detector are compared. The self-developed silicon semiconductor γ dose rate monitor can meet the monitoring requirements of different reactor types and has a good application prospect.